Worst Case Scenario - Newman, T. J., (Novelist) (New York : Little, Brown and Company, 2024)
"When a pilot suffers a heart attack at 35,000 feet, a commercial airliner filled with passengers crashes into a nuclear power plant in the small town of Waketa, Minnesota, which becomes ground zero for a catastrophic national crisis with global implications....The International Nuclear Event Scale tracks nuclear disasters. It has seven levels. Level 7 is a Major Accident, with only two on record: Fukushima and Chernobyl. There has never been a Level 8. Until now....[O]rdinary people-power plant employees, firefighters, teachers, families, neighbors, and friends- are thrust into an extraordinary situation as they face the ultimate test of their lives. It will take the combined courage, ingenuity, and determination of a brave few to save not only their community and loved ones, but the fate of humanity at large." --publisher's website.
new book 2024 summer.
Keywords: Aircraft accidents -- Fiction; Nuclear accidents -- Fiction; Emergency management -- Fiction; Human beings -- Extinction -- Prevention -- Fiction; Survival; Minnesota -- Fiction; Thriller fiction; Suspense fiction